Redescriptions of six Japanese species of the genus Pulvinaria (Hemiptera: Coccomorpha: Coccidae) with four new synonymies - Tanaka, Hirotaka; Kamitani, Satoshi (Zootaxa, 2021)
Six Japanese species of the genus Pulvinaria Targioni Tozzetti (Hemiptera: Coccomorpha; Coccidae): P. aurantii Cockerell, 1896, P. hazeae Kuwana, 1902, P. idesiae Kuwana, 1914, P. kuwacola Kuwana, 1907, P. nipponica Lindinger, 1933 and P. photiniae Kuwana, 1914, are redescribed and illustrated based on type specimens and some newly collected adult females. In addition, Pulvinaria decorata Borchsenius, 1957 syn. nov. and P. ornata Froggatt, 1921 (nec Hempel, 1912) syn. nov. are proposed as new junior synonyms of P. aurantii, and Pulvinaria fujisana Kanda, 1960 syn. nov. and P. hydrangeae Steinweden, 1946 syn. nov. are proposed as new junior synonyms of P. kuwacola. Lectotypes are designated for P. idesiae, P. nipponica and P. photiniae from the syntypes of these species and, in the absence of any original material, neotypes are designated for P. hazeae and P. kuwacola, respectively, using specimens collected from the type localities. To facilitate comparisons, a table containing diagnostic morphological character states of the redescribed species and the type species of the genus, P. vitis (Linnaeus, 1758), is provided.